APPRAISING FABRICATION AND WELDING STUDENTS’ EMPLOYABILITY SKILLS IN OGUN STATE TECHNICAL COLLEGES - Olawale, Olakotan Olusegun; Olaseni, Lemo Olusiji (UPI Press, 2019)
This study appraised fabrication and welding students’ employability skills in Ogun State technical colleges. Two research questions were raised in relation to the focus of the study. A structured Questionnaire containing 15 items was developed and used for data collection. The questionnaire was validated by 3 experts and tested for reliability using Cronbach Alpha Coefficient at 0.96. The questionnaire was used for collecting data from 57 respondents made by fabrication and welding industrial-based supervisors in Ogun State. The data collected were analyzed using descriptive statistics of mean and standard deviation to answer the research questions raised in the study. The study affirmed that fabrication and welding students in Ogun State technical colleges possessed sheet metalwork skills and gas welding skills. The study recommended among others that adequate supervision and monitoring of TVET institution’s students on industrial attachment should be ensured by TVET institution’s administrators and that industrial-based supervisors should be objective in discharging their duties during students’ industrial attachment period.